James Baldwin’s “Somber Question” and “Befriending the Fallen” in Türkiye - Özge Özbek Akıman (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
Departing from the United States in 1948, James Baldwin (1924-1987) lived intermittently in Istanbul between 1961 and 1971. Baldwin’s Turkish experience comes into being through his friendship with the Turkish actor Engin Cezzar, whom Baldwin met in the late 1950s in New York City. Commissioned to write about racial relationships on a larger scale, including the Middle East and Africa, Baldwin began to travel in 1961. As he explored the colonized geography, he faced, in his words, a “somber question” about African Americans’ role inside and outside the United States in relation to civil rights struggles. Unable to handle the question, he flew to Turkey. Acknowledging Turkey as a beneficiary of American financial aid against Soviet influence, Baldwin was furiously critical of American claims to freedom and democracy. His stay in Istanbul marks the period in which Baldwin evaluates racism as a historical and global component of colonialism that goes beyond the civil rights struggles in the US. Substantially written in Istanbul, No Name in the Street reflects this broadscale critique. Additionally, our theater history bears Baldwin’s traces as he directed Düşenin Dostu, produced by the Sururi-Cezzar Theater. As an important chapter in Turkish theater, the production manifests Baldwin’s interest in the theater and the imprisonment theme. This essay examines the Baldwin–Turkey link with reference to No Name in the Street and the production of Düşenin Dostu. In addition to the traces preserved in the theater archives, what Baldwin left in Turkey was a critique that counters American triumphalism.